2014
DOI: 10.1371/journal.pone.0089030
|View full text |Cite
|
Sign up to set email alerts
|

GmFT4, a Homolog of FLOWERING LOCUS T, Is Positively Regulated by E1 and Functions as a Flowering Repressor in Soybean

Abstract: The major maturity gene E1 has the most prominent effect on flowering time and photoperiod sensitivity of soybean, but the pathway mediated by E1 is largely unknown. Here, we found the expression of GmFT4, a homolog of Flowering Locus T, was strongly up-regulated in transgenic soybean overexpressing E1, whereas expression of flowering activators, GmFT2a and GmFT5a, was suppressed. GmFT4 expression was strongly up-regulated by long days exhibiting a diurnal rhythm, but down-regulated by short days. Notably, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 65 publications
2
94
0
2
Order By: Relevance
“…Recently, numerous studies have provided major insight into the genetic mechanism controlling soybean response to photoperiod, and found that E3 and E4 genes, which encode the photoreceptors GmPHYA3 and GmPHYA2 respectively, upregulate almost all photoperiodic flowering identity genes in soybean (Liu et al 2008;Watanabe et al 2009;Kong et al 2010;Sun et al 2011;Xia et al 2012b;Zhai et al 2014). Consequently, we examined the expression of GmTOE4a in E3 and E4 NILs, including the e3 and e4 single or double mutant, and observed that GmTOE4a was upregulated by E3 and E4 (Fig.…”
Section: The Role Of Gmtoe4a In Photoperiodic Floweringmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, numerous studies have provided major insight into the genetic mechanism controlling soybean response to photoperiod, and found that E3 and E4 genes, which encode the photoreceptors GmPHYA3 and GmPHYA2 respectively, upregulate almost all photoperiodic flowering identity genes in soybean (Liu et al 2008;Watanabe et al 2009;Kong et al 2010;Sun et al 2011;Xia et al 2012b;Zhai et al 2014). Consequently, we examined the expression of GmTOE4a in E3 and E4 NILs, including the e3 and e4 single or double mutant, and observed that GmTOE4a was upregulated by E3 and E4 (Fig.…”
Section: The Role Of Gmtoe4a In Photoperiodic Floweringmentioning
confidence: 96%
“…In addition, GmFT2a and GmFT5a are involved in photoperiod-regulated flowering and coordinately promote flowering, while GmFT4 acts as a negative regulator of flowering time in soybean (Kong et al 2010;Zhai et al 2014). Given the late flowering phenotype observed in the 35S::GmTOE4a plants, we hypothesized that flowering time genes would be repressed in the transgenic plants.…”
Section: Gmtoe4a Regulates Some Key Flowering-related Genes In Soybeanmentioning
confidence: 99%
“…This gene family has been studied in several legume species (Kong et al, 2010;Hecht et al, 2011;Laurie et al, 2011;Yamashino et al, 2013;Zhai et al, 2014), where most species have at least five FT-like genes that may be divided into three distinct clades: FTa, FTb, and FTc . We identified five members of this family in chickpea and observed clear differences in their expression between ICCV 96029 and CDC Frontier.…”
Section: The Expression Of Ft Genes Is Misregulated In a Line Carryinmentioning
confidence: 99%
“…Soybean possesses at least 10 FT homologs, which are arranged as five pairs of linked genes in different homologous chromosomal regions (Kong et al, 2010). At least six of these genes promote early flowering when they are ectopically expressed in Arabidopsis (Kong et al, 2010;Thakare et al, 2011;Fan et al, 2014), whereas FT4 has an antagonistic effect (Zhai et al, 2014). Among these six genes, only FT2a and FT5a exhibit transcriptional patterns closely associated with changes in photoperiod (Kong et al, 2010).…”
mentioning
confidence: 99%